Using Paratextualization to Build a Cultural Scheme of Brands for the Entertainment In-dustry - de Souza-Leão, André Luiz Maranhão; Moura, Bruno Melo; Lopes, Mariana Almeida de Souza; Batista, Marília Abigail Meneses; Melo, Maria Eduarda da Mota; Santos, Juliana Francisca Dutra dos (Revista de Negócios, 2023)
Media product franchises often play the role of brands based on the elaboration of cultural schemes. They use complementary contents to their products’ narratives – called paratexts – to keep a long-lasting relationship with their consumers. Thus, the aim of the current study is to investigate how the paratextualization of franchise products of the entertainment industry generates cultural schemes for their brands. To do so, Foucauldian Discourse Analysis was applied to news reports and information published at the official websites of three emblematic entertainment industry franchises: Game of Thrones, Star Wars and Wizarding World. Results have indicated franchises’ focus on maintaining and expanding fans’ experience with these sagas, evidencing the existence of a cultural scheme to build experiential brands.